Investigating University Students' Failure in English Requirement Courses - Jamal Kaid Mohammed Ali (مجلة الدراسات الاجتماعية, 2019)
Some university students might fail at their first attempt to study English requirement courses, but later they perform well, ultimately recognizing that the courses were easy and their failure in such simple courses was a great loss. Others continue failing, get frustrated and finally may quit trying. The purpose of the current study, therefore, was to investigate the factors that contribute to university non-English major students' failure in English courses. A mixed model questionnaire was used to collect data from 56 male students who failed English at the University of Bisha, Saudi Arabia. All participants had previously failed English and were repeating the English requirement course during the period of data collection. Results of the study revealed that factors such as teachers, anxiety and inappropriate study methods were more responsible for students' failure than motivation, friends and family problems. Results also showed a significant difference between students who only failed the English course and those who failed two or more other courses. Those who failed two or more courses scored higher on anxiety than those who failed only English. Recommendations were that English teachers should be trained to follow collaborative learning and student-centered approaches and that the English curriculum for non-English major students should reflect their major.